HUMAN BEHAVIOUR AS AN OBJECT OF INTERDISCIPLINARY RESEARCH - Alimuhammedova Khabiba Rustamovna (Scholar Express Journal, 2021)
The article proves that human behaviour has been studied theoretically and practically as an object of interdisciplinary research. It was also noted that behaviour is studied in various fields of social and humanitarian sciences: philosophy, sociology, in particular, psychology and linguistics.
Keywords: Human Behaviour; Social Sciences; Humanities; Philosophy